Political Philosophy in Borges: Fallibility, Liberal Anarchism, and Civic Ethics - Salinas, Alejandra M. (2010)
Fil: Salinas, Alejandra M. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales; Argentina